Transformative Da'wah Communication for Marginalized Communities: A Case Study of Majelis Sabilu Taubah - Wahyudi, Ruhan; Nur Afni Khafsoh; Matroni (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2026)
This study examines the transformation of socio-religious consciousness among marginalized communities through the Majelis Sabilu Taubah, Blitar, led by Gus Iqdam. The phenomenon under investigation involves revitalizing religious meaning and social inclusion for individuals who are often excluded from formal religious spaces. The research focuses on how Sabilu Taubah reconstructs cultural and religious values through inclusive da’wah practices and participatory community engagement. Employing a qualitative case study approach, primary data were collected through in-depth interviews, participant and non-participant observation, and systematic documentation. These data were then analyzed using the theoretical framework of social construction by Berger & Luckmann and the concept of the “global village” by McLuhan. The findings indicate that Gus Iqdam’s approach, characterized by accessible language, humor, and cultural sensitivity, facilitates the externalization, objectification, and internalization of religious and social values among marginalized groups. The process leads to positive changes in personal attitudes, enhanced solidarity, and the reintegration of former street dwellers, ex-punks, and marginalized individuals into broader society. This study highlights the pivotal role of inclusive religious communities in fostering socio-cultural transformation and sustained empowerment of previously marginalized populations, leveraging digital platforms.